Salivary vitamin D levels in children with autism in relation to oral health status and disease severity - Jehan Y Al-Demirchi; Batool H Al-Ghurabi; Waqar AlKubaisy (Journal of Baghdad College of Dentistry)
Background: Autism spectrum disorder is characterized by difficulties with social interaction and communication, as well as limited patterns of behavior and atypical sensory sensitivity. Although vitamin D insufficiency has previously been observed in autistic children, evidence on the link between vitamin D deficiency, oral health condition, and autism severity is scarce. The purpose of this study was to investigate vitamin D levels in relation to oral health status of children with autism, as well as the relationship between vitamin D and disease severity. Materials and  methods: Two groups  were  included  in  this study:  40 institutionalized  autistic children as a study group and 40 apparently healthy children as a control group with  age  range  (3-12)  years.  Depending on the severity of autistic symptoms, the group was classified into three subgroups: mild, moderate, and severe. The oral examination was performed using simplified oral hygiene and decayed, missing and filled tooth indices to measure oral health status for both groups. Three millilitres of un-stimulated salivary sample was taken by drooling technique, the salivary level of vitamin D assessed by enzyme-linked immunosorbent assay. The data from the current study were analysed using SPSS version 21. Results: Salivary vitamin D levels were found to be significantly lower in the study group than in the control group. This reduction was not correlated with the severity of autism. 37.5% of the autistic patient group had fair oral hygiene, compared to 20% of the control group; simplified oral hygiene index shows negative significant correlation with vitamin D level while caries experience was significantly higher in patient group and there was a negative non-significant correlation with vitamin D level. Conclusion: The vitamin D level was significantly lower in the patient group with no correlation with disease severity, fair oral hygiene and more caries in both primary and permanent dentition was observed in autistic patients with significant negative correlation between the simplified oral hygiene index and vitamin D, while negative non-significant correlation with dental caries